Library collaborative partnership of three O.P. Sienna Schools a gateway to O.P. Sienna Schools Library System - Delos Santos, Myra D. (2008)
We are inexorably trapped in an era of change from a simple teaching and learning lifestyle to technologically invaded education that seemingly turns everything around overwhelmingly electronic Communications become synonymously equated to fast and instant delivery of information. In effect, educational institutions for their part will have to take an innovatory move to meet the complex demands of its clientele and its environment. The administrators, on the other hand, will have to strive to meet the standards of the new trend in the convergent modes of making the information resources available and the means provided to access these resources. Such standards are gained through new resolves of seeking competencies no longer in independence and rivalries but by partnership, collaboration and by all means, concerted efforts with other institutions. Thus, it is in this light that this study is focused on the Library collaborative partnership of three OP Siena Schools that will hopefully start the O.P. Siena Schools Library System. It is meant to build a collaborative endeavor of resource sharing among the sister-schools of the OP Siena Congregation where all schools are members and beneficiaries notwithstanding its individual's resource and financial contributory capability.